2012
DOI: 10.1177/147323001204000306
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Levels of Follistatin in Patients with Ovarian Cancer

Abstract: The serum FST level was elevated in the peripheral blood of patients with ovarian cancer and has potential as a tumour marker for ovarian cancer diagnosis. It may be particularly useful when combined with CA-125 detection to reduce the number of false-positive results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…These findings provoked studies investigating FST as a diagnostic or prognostic marker for solid tumours. One study showed that serum FST and ovarian carcinoma antigen CA125 levels were significantly increased in patients with ovarian cancer when compared with healthy individuals and patients with benign ovarian cysts, which suggests that the serum FST level has potential diagnostic value, especially when combined with CA125 detection in order to reduce the number of false-positive results (105). Serum levels of FST were also found to be elevated in patients with hepatocellular cancer (HCC) (21,106).…”
Section: Value Of Follistatin In Diagnosis Prognosis and Of Solid Tumentioning
confidence: 99%
“…These findings provoked studies investigating FST as a diagnostic or prognostic marker for solid tumours. One study showed that serum FST and ovarian carcinoma antigen CA125 levels were significantly increased in patients with ovarian cancer when compared with healthy individuals and patients with benign ovarian cysts, which suggests that the serum FST level has potential diagnostic value, especially when combined with CA125 detection in order to reduce the number of false-positive results (105). Serum levels of FST were also found to be elevated in patients with hepatocellular cancer (HCC) (21,106).…”
Section: Value Of Follistatin In Diagnosis Prognosis and Of Solid Tumentioning
confidence: 99%
“…FST is a specific binding protein of activin and is involved in the regulation of pathophysiological functions, including early embryonic development and differentiation of ovarian granulosa cells . A recent study suggested that FST protein expression was immunohistochemically detected in 53% of ovarian cancers, and that high serum levels of FST were found in the patients . Therefore, we study histopathological features of the FOXL2 p.C134W mutation‐positive and ‐negative GCT regarding the expression of BMP2 and FST immunohistochemically.…”
Section: Introductionmentioning
confidence: 98%
“…FST binds activin to inhibit its activity 34) , and dysregulation of the FST and activin axis is one of the most significant factors underlying tumor genesis. FST has been reported as a biomarker or therapeutic target in cancers such as breast cancer 35) , ovarian cancer 36,37) , hepatocellular carcinoma 23) , and glioblastoma 38) . Recently, Chen et al reported that FST is a novel biomarker for the diagnosis of lung adenocarcinoma 22) .…”
Section: Discussionmentioning
confidence: 99%